s = d(sec-1(x))/dx = 1/x*sqrt(x^2 - 1)
c = d(csc-1(x))/dx = - 1/sqrt(x^4 - x^2)
Answer = s - c
Answer = 1/x*sqrt(x^2 - 1) + 1/sqrt(x^4 - x^2)
Answer = 1/x sqrt(x^2 - 1) + 1/x*sqrt(x^2 - 1)
Answer = 1/x sqrt(x^2 - 1) * [1 + 1]
Answer = 1/2*x*sqrt(x^2 - 1)
f'(x) = 2/[x sqrt(x^2 - 1)]
Now you are ready to put in values for f'(x)
f'(4) = 2/[ 4 sqrt(16 - 1)]
f'(4) = 2/[ 4 sqrt(15)
f'(4) = 1/2 * sqrt(15)/15
f'(4) = sqrt(15)/30
f'(-1) = 2/(-1) sqrt( ((-1)^2 - 1)
Undefined. I don't know how you've been instructed to handle 1/0. I call it undefined.
f'(1/2) = 2/((1/2)sqrt(1/2)^2 - 1) another undefined.
f'(1/2) = 4/(sqrt(1/4 - 1)
f'(1/2) = 4/sqrt(-3/4)
f'(1/2) = 8/ i*sqrt(3)
f'(1/2) = 8* sqrt(3) / 3*i
f'(1/2) = 8*i* sqrt(3)/3*i^2
f'(1/2) = - 8i sqrt(3) / 3